Answer:
-2/3
Step-by-step explanation:
1 2/3 - 2 1/3
5/3 - 2 1/3
5/3 - 7/3
-2/3
Answer: y = -0.2(x - 2.25)² + 1.6125
<u>Step-by-step explanation:</u>
Answer:
<u>4(1 – x) + 2 x = -3( x + 1)</u>
first do 4 time 1= 4
then do 4 times x =4x
now the equation should look like this
4-4x+2x=-3(x+1)
then do the other side of the equation
-3(x+1)
=-3x-3
Now collect the like terms:
-4x-2x
now the equation should look like this
4-2x=-3x-3
now add 3x add on both sides
4-2x+3x=-3
put the 4 on the other side
-2x+3x=-3-4
now again collect the like terms (-2x+3x=1 which is just x and -3-4 =-7)
x=-7
answer
x=-7